2022
DOI: 10.3390/cosmetics9020039
|View full text |Cite
|
Sign up to set email alerts
|

Phytocosmetic Emulsion Containing Extract of Morus nigra L. (Moraceae): Development, Stability Study, Antioxidant and Antibacterial Activities

Abstract: Morus nigra L. is a species popularly known in the Northeast of Brazil as “amora miúra”. This species is a source of flavonoids with antioxidant activity. Antioxidants play an important role in the preservation of cosmetic formulations, and they neutralize free radicals. The objective of this study was to develop a topical emulsion containing leaf extract of Morus nigra L., as well as to evaluate the stability, antioxidant and antibacterial activities of the formulations. A crude hydroalcoholic (70%) extract o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…However, after FDC, it was possible to observe a considerable loss of antioxidant capacity in all formulations, showing that the bioactive extract evaluated in this study is very sensitive to temperature variation. A study that evaluated the antioxidant activity of the hydroalcoholic extract of Morus nigra incorporated in an emulsion of the O/W type, in environments with different temperatures: refrigerator, shelf and oven, observed that after 90 days in the refrigerator, there was a considerable drop in the antioxidant capacity of the formulation (38).…”
Section: Resultsmentioning
confidence: 99%
“…However, after FDC, it was possible to observe a considerable loss of antioxidant capacity in all formulations, showing that the bioactive extract evaluated in this study is very sensitive to temperature variation. A study that evaluated the antioxidant activity of the hydroalcoholic extract of Morus nigra incorporated in an emulsion of the O/W type, in environments with different temperatures: refrigerator, shelf and oven, observed that after 90 days in the refrigerator, there was a considerable drop in the antioxidant capacity of the formulation (38).…”
Section: Resultsmentioning
confidence: 99%
“…Interest in spices and aromatic and other plants, which are natural sources of antioxidants, has increased in recent years (Aboukhalaf et al, 2020(Aboukhalaf et al, , 2022Neves et al, 2021;Mechqoq et al, 2022;Melo et al, 2022;Munekata et al, 2022;Özogul et al, 2022). Natural plant extracts are used in the food industry as alternative preservatives.…”
Section: The Preservative Effects Of Eos On Chicken and Seafood Productmentioning
confidence: 99%
“…Various morphological parts of mulberry such as leaves, fruits, roots and stems have been used for different purposes (7). Morus nigra L. (Moraceae), known as ''black mulberry" or "wild mulberry" belongs to the genus Morus and used as an expectorant, antiseptic, sedative, diuretic, laxative antioxidant, and anthelmintic (8,9). It has important effects due to the presence of flavonoids, tannins, coumarins, triterpenoids and steroids in its composition (10).…”
Section: Introductionmentioning
confidence: 99%